Costa rican pot-honey: Its medicinal use and antibacterial effect - Zamora Fallas, Luis Gabriel (2012)
There are very few records on the use of pot-honey by indigenous people of Costa Rica. Our evaluation concerns antimicrobial activity of honey samples from Tetragonisca angustula, Melipona beecheii and Apis mellifera, performed to determine whether traditional appreciation of stingless bee honey from Costa Rica, over that of A. mellifera honey, is justified by this criterion. The stingless bee honeys were more active than that of A. mellifera against Staphylococcus aureus and Pseudomonas aeruginosa―currently the major causes of burn and wound infections. The results presented herein are among the first steps towards further study of antimicrobial components in Costa Rican stingless bee honey.